Comparison of personality trait and emotional intelligence between the women who experienced domestic violence and control group - Seyyedyan, Marzieh; Moosazadeh , Tavakol; Narimani Mostaali Begloo, Mohammad (Journal of Education Culture and Society, 2021)
Aim. The aim of this research is comparing the role of personality traits and emotional intelligence between women who experienced domestic violence and  a control group.Methods. The statistical population of the study includes all women (700 participants) referred to the judicial authorities of Ardabil province in 2019.The research sample included 30 women who experienced domestic violence and 30 women as control group (not experienced domestic violence) who were selected by available sampling method. To measure emotional intelligence and personality traits, the Bar-on Emotional Intelligence Questionnaire and NEO Questionnaire was used. The questionnaires briefly describe and evaluate the two complex concepts of emotional intelligence and current emotional health. Data analysis was performed using SPSS statistical software and MANOVA. The main variables of the research were neuroticism, extroversion, openness, agreeableness, extra-individual skills, conscientiousness, interpersonal skills, adaptability, stress control and public mood.Results. The findings of the research have shown that among the characteristics of the five major personality factors (NEO), only the neuroticism component was more prevalent among women who experienced domestic violence, and the rest of the personality traits (extroversion, agreeableness, conscientiousness, and openness to new experiences) among control group were higher (P